#metoo 2.0 to #meNOmore: Analysing Western Reporting About Sexual Violence in the Music Industry. (7th February 2020) - Baker, Andrea; Williams, Katrina; Rodrigues, Usha M.
ABSTRACT: In October 2017, #metoo 2.0 reinforces the gendered sexual violence in the creative sector [Marghitu, 2018 . "It's Just art: Auteur Apologism in the Post-Weinstein era", Feminist Media Studies, 18(93): 491–494] Building on this movement, on 11 November that year, 2912 women "testified about the situation in the Swedish music industry", signing an open letter condemning sexual violence [Nyheter, 2017. "2192 Women in the Swedish Music Industry Behind Appeal Against Sexism." Dagens Nyheter, November 17. https://www.dn.se/kultur-noje/2192-women-in-the-swedish-music-industry-behind-appeal-against-sexism/ ]. After the Swedish initiative, on 12 December 2017, the #meNOmore hashtag was established by 1000 women who signed an open letter to the Australian music industry speaking out against similar behaviour [Whyte, 2017a . "Artists Speak Out Against Sexual Harassment in the Music Industry." AM – ABC Radio, December 13. https://www.abc.net.au/radio/programs/am/sexual-harassment-in-the-music-industry/9253956]. Using a content analysis framework, this study examines the media framing of 26 stories about #meNOmore by the Western press from 22 November 2017 (height of the Swedish campaign) to 21 December 2017 (a week after the hashtag surfaced in Australia). Research from journalism studies and musicology highlights that sexual violence is historically engrained in the media and music industries. However, findings from our study of the first month's coverage of the #meNOmore content analysis in 2017 reveal that media reports about women and sexual violence were framed around addressing gender inequality and systemic structural issues in the music industry. This raises the question, has the media has turned a corner when covering sexual violence in the post #metoo era?